Mental Representations and Cognitive Schemata of Ninth Grade Students for the Refraction of Light - George Fyttas; Vassilis Komis; George Kaliampos; Konstantinos Ravanis (MDPI AG, 2023)
The current research study deals with students' mental representations and cognitive schemata of light refraction. In the study, 213 ninth grade students participated who had taken basic Geometric Optics courses on refraction and Snell's law. The students were given three tasks in which they were asked to predict and explain the phenomenon of refraction. The results showed that the vast majority of them articulated their responses based on representations that were not compatible with the Geometric Optics model. Quite interestingly, the Multiple Correspondence Analysis led to five distinct cognitive schemata resulting from a fixed combination of representations.